Devastating salt‐wasting crisis in a four‐month‐old male child with congenital adrenal hyperplasia, highlighting the essence of neonatal screening. Issue 7 (11th July 2022) - Reddy, Nagaspurthy Anugu; Sharma, Sucheta; Das, Mainak; Kapoor, Ashutosh; Maskey, Upasana
Abstract: Congenital adrenal hyperplasia (CAH) is a rare condition usually referred to as a group of genetic disorders resulting due to a deficiency of steroid enzymes required by adrenal glands to produce cortisol and mineralocorticoid hormones. It has an autosomal recessive mode of inheritance and is further categorized into two types—Classic and Non‐Classic. Non‐Classic CAH is a more common milder form that presents late after puberty. Classic CAH, although more severe, is rare and detected at birth and is associated with the life‐threatening adrenal crisis in both sexes and virilization of the external genitalia in females (46, XX) patients, whereas in males, no overt abnormality of the external genitalia is present. We present a case of a four‐month‐old male child with the classic form of CAH who was brought with complaints of loose stools, projectile non bilious vomiting, decreased urine output, and failure to feed for 3 days. The child had a clinical presentation of salt wasting with hypoglycemia and hyperpigmentation of his genitalia. The USG findings revealed increased anteroposterior diameter of renal pelvis indicative of a growth in the suprarenal area. 17‐hydroxyprogesterone (17‐OHP) was found to be elevated confirming the diagnosis. He was treated with hydrocortisone with gradual improvement in his glucose and electrolytes. The patient was discharged home on replacement therapy consisting of oral prednisolone and fludrocortisone acetate and followed up as outpatient with significant improvement in the clinical findings. The fact that the child was not screened for CAH at birth led to the critical consequences of the disease in this case. To prevent life‐threatening adrenal crisis and help perform appropriate sex assignments for affected female patients, newborn screening (NBS) programs for the classical form of CAH should be made mandatory even in low‐ and middle‐income countries. Abstract : Congenital adrenal hyperplasia although rare can present with a devastating salt‐wasting crisis, virilization of females, and failure to thrive. Early diagnosis through screening at birth can yield better outcomes. This case highlights the need for mandatory screening in low‐ and middle‐income countries.